Regional Office Administration System (SISMINKADA) as a Solution for Archives Management in the Special Region of Yogyakarta - Slamet Hari Sutanto (Inovbook Publications, 2021)
This research is about development governance, namely the Regional Development Planning Information System. Of course, to create optimal development, concerning all aspects of the pre-facilities facility to maximize the economic potential in the region. This study used qualitative research methods. The population in this study are areas that have innovative development planning. Meanwhile, the research subjects are in South Sulawesi Province which has the Innovation of the Regional Development Planning Information System (SIPPD) and in East Java Province which has innovation named Arabica cabinet (collaborative collateral for Arabica Coffee Integrated Economic Development). The results of this study indicate that the innovation of the Regional Development Planning Information System (SIPPD) conducted by South Sulawesi Province has succeeded in achieving the designation that has been designed. Likewise the Arabica cabinet innovation (collaboration of the Integrated Economic Development of Arabica Coffee) in East Java Province has succeeded in optimizing land in its area and conducting counseling, education, training, sustainable assistance, and the assistance of coffee processing tools / machines.